PENGARUH KUALIFIKASI AKADEMIK DOSEN TERHADAP MUTU PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (Telaah Hasil Penelitian dan Kajian Tindak Lanjut) - Dahlan Lama Bawa (JIE (Journal of Islamic Education), 2020)
This article is a review of the results of research and follow-up studies of the results of research on the Effects of Lecturer Qualifications and Lecturer Academic Achievement on the Quality of Learning in 2019 at Muhammadiyah University Makassar. This type of research is the Library Research (qualitative research) qualitative approach by making the results of quantitative research on the Effects of Lecturer Qualifications and Lecturer Academic Achievement on Learning Quality in 2019 at Muhammadiyah University Makassar as the main reference. The results of this study and follow-up study found two main points that deserve the attention of academic people, namely: 1) efforts to improve the quality of PAI learning, so in appointing Lecturers and giving lecturers of PAI, it is necessary to consider factors related to the quality of learning, 2) learning is a complicated process, including in PAI learning, it is necessary to pay attention to the principles and indicators of learning quality in accordance with UNESCO guidelines.